PENGARUH SERVICE QUALITY, PRICE, PRODUCT VARIETY, DAN PLACE TERHADAP DECISION TO USE PADA TOKO ANEKA VARIASI - Tjandra, Marcelino; Effendy, Junko Alessandro (Universitas Ciputra Surabaya, 2023)
The purpose of this research is to find out the effect of service quality, price, product variety, and place on decision to use at Toko Aneka Variasi. The variables of this research are Service Quality, Price, Product Variety, and Place as independent variables and Decision to Use as dependent variable. The research method that is used is multiple linear regression analysis. Data collection method of this research is by distributing digital questionnaires through Google form to 335 respondents of the population of 13.502 customers of Toko Aneka Variasi calculated from July 2022 to February 2023. The results of this research are service quality, price, and product variety variables affects positive and significant on decision to use at Toko Aneka Variasi. However, place variable does not affect significant on decision to use at Toko Aneka Variasi. The result of this research are referred to the owner of Toko Aneka Variasi. Keyword: Service Quality, Price, Product Variety, Place on Decision to Use